(untitled) (Research, Society and Development, 2022)
The purpose of this study was to understand, through scientific evidence, the types of root resorption arising from the reimplantation of avulsed tooth, and to analyze the factors that contribute to its development. PubMed and LILACS databases were searched using the keywords "Root resorption", "Toothreimplantation", "Incidence" and "Avulsion" using the Boolean operator "AND". The search included articles published in the database in the last five years in English. The search resulted in 461 articles, leaving 94 articles after the selection of articles published from 2016 to 2021. The selection of articles was guided by reading the titles and abstracts, and 22 articles were selected for reading in full. Finally, 8 articles were included in this integrative review, corresponding to the eligibility criteria. Despite the lack of standardization of studies, it was found that RR related to the reimplantation of avulsed teeth had a higher incidence of external RR. As for the types of external RR, the articles showed higher incidence for RR by replacement, as well as its relationship in cases of lost/extracted teeth. However, not all studies classified the factors related to RR, making it difficult to perform a subgroup analysis to determine the major causal relationship and tooth loss. Therefore, further clinical analysis studies need to be conducted in a standardized manner, so that a more accurate analysis of the incidence as well as the reasons why dental elements developed and were lost/extracted by RR can be performed.